Following momentum and avoiding the "Minsky Moment" evidence from investors on the Financial Instability Hypothesis. (1st August 2016) - Pirie, Scott; Chan, Ronald King To
Abstract : Purpose: This study aims to find out how institutional investors use momentum in making investment decisions, and whether their actions are consistent with the Financial Instability Hypothesis of Hyman Minsky. Design/methodology/approach: The study discusses the findings of interviews with 25 professional investors from the Hong Kong offices of five global financial institutions. All of the participants have several years of practical experience in global and regional markets. Findings: Nearly all the managers interviewed said they use momentum in making investment decisions, and they do this in ways that are consistent with the Financial Instability Hypothesis, in which markets alternate between stable and unstable states. The participants are aware they may contribute to this, but they cannot avoid doing it because of short-term constraints in the present financial system. Originality/value: This study adds to our knowledge of how professional investors use momentum in their investment strategies. It complements findings of quantitative studies that show momentum strategies have been profitable in many market settings. It also adds evidence that supports the Financial Instability Hypothesis.